A mainstreaming oncogenomics model: improving the identification of Lynch syndrome - O’Shea, Rosie; Crook, Ashley; Jacobs, Chris; Kentwell, Maira; Gleeson, Margaret; Tucker, Katherine M.; Hampel, Heather; Rahm, Alanna Kulchak; Taylor, Natalie; Lewis, Sarah; Rankin, Nicole M. (Frontiers in Oncology, 2023)
Introduction: ‘Mainstreaming’ is a proposed strategy to integrate genomic testing into oncology. The aim of this paper is to develop a mainstreaming oncogenomics model by identifying health system interventions and implementation strategies for mainstreaming Lynch Syndrome genomic testing. Methods: A rigorous theoretical approach inclusive of conducting a systematic review, a qualitative and quantitative studies were undertaken using the Consolidated Framework for Implementation Research. Theory-informed implementation data were mapped to the Genomic Medicine Integrative Research framework to generate potential strategies. Results: The systematic review identified a lack of theory-guided health system interventions and evaluation for Lynch syndrome and other mainstreaming programs. The qualitative study phase included 22 participants from 12 health organisations. The quantitative Lynch syndrome survey included 198 responses: 26% and 66% from genetic and oncology health professionals, respectively. Studies identified the relative advantage and clinical utility of mainstreaming to improve genetic test access and to streamline care, adaptation of current processes was recognized for results delivery and follow up. Barriers identified included funding, infrastructure and resources, and the need for process and role delineation. Interventions to overcome barriers were: embedded mainstream genetic counsellors, electronic medical record genetic test ordering, results tracking and mainstreaming education resources. Implementation evidence was connected through Genomic Medicine Integrative Research framework resulting in a mainstreaming oncogenomics model. Discussions: The proposed mainstreaming oncogenomics model acts as a complex intervention. It features an adaptable suite of implementation strategies to inform Lynch syndrome and other hereditary cancer service delivery. Implementation and evaluation of the model is required in future research.